Inovasi Media Pembelajaran Matematika: Pemanfaatan Android dan Adobe Animate untuk Peningkatan Literasi Siswa pada Relasi dan Fungsi - -, Sutra; Majid, Ahmad Farham; Shadiq, Muh Ibnu; Kurniati (Universitas Muhammadiyah Prof. DR. HAMKA, 2025)
Purpose: This research aims to develop and evaluate the effectiveness of mathematics learning media utilizing Android and Adobe Animate on the topic of relations and functions, specifically to address the prevailing deficiency in students' mathematical literacy. Design/methodology/approach: The study employs a Research and Development (R&D) technique guided by the ADDIE model, encompassing the phases of analysis, design, development, implementation, and evaluation. The research subjects consisted of 21 tenth-grade students at MA Madani Pao-Pao, utilizing instruments such as expert validation sheets, teacher and student response questionnaires, and pretest-posttest assessments. Findings: The validation results for both media and content demonstrated